Artificial intelligence driven 6G networks:endogenous intelligence - Tong ZHANG; Yijing REN; Shi YAN; Mugen PENG (Dianxin kexue)
In order to meetthe requirements of intelligently adapting to the needs of human-machine-thing deep interconnection,the sixth-generation mobile communication system (6G) will be based on full spectrum,face all scenarios and support all services.Endogenous intelligence is the core component of 6G and an inevitable trend driving 5G evolution.The characteristics and compositions of artificial intelligence driven 6G endogenous intelligent networks were discussed.The key technologies of endogenous intelligent network and current status of industrial applications were also described.Further,domestic and foreign related progress and standardization works were introduced,and also position future challenges were prospected.